Development and Use of IgM/J‐Chain Fusion Proteins for Characterization of Immunoglobulin Superfamily Ligand‐Receptor Interactions. Issue 1 (3rd February 2014) - Ammann, Johannes U.; Trowsdale, John
Abstract: Discovery of binding partners for immunoglobulin molecules expressed by cells of the immune system is an important topic of current research. However, many ligand‐receptor interactions are of low affinity, and hence detection is refractory to most established protocols. We evaluated fusion proteins based on human IgM as high avidity probes to screen for ligand‐receptor binding. We describe methods for cloning, expression, and quantification of IgM fusion proteins with J‐chain. Furthermore, we outline protocols to assess binding of IgM fusion proteins to cells and to plate‐bound proteins. Compared to standard IgG‐fusion proteins, IgM + J chain increased binding of a test interaction, PD‐L1 to PD‐1, up to 1000‐fold. Curr. Protoc. Protein Sci . 75:19.24.1‐19.24.11. © 2014 by John Wiley & Sons, Inc.